PERCEPTIONS OF BENEFICIARY FAMILIES OF INTEGRATED SOCIAL PROTECTION SERVICES IN POVERTY ALLEVIATION THROUGH CENTER OF SOCIAL WELFARE (PUSKESOS) (CASE STUDY OF SABILULUNGAN INTEGRATED SERVICE AND REFERRAL SYSTEM (SLRT) PROGRAM IN BANDUNG REGENCY) - Denti Kardeti; Budhi Gunawan; Binahayati Rusyidi; Mira Azzasyofia (Politeknik Kesejahteraan Sosial Bandung, 2020)
This study shows the factors that influence integrated social protection services from the perspective of the beneficiaries at integrated and referral system (SLRT) in Bandung Regency. Respondents of this study were 284 beneficiaries of integrated social protection services. This research uses quantitative research methods. The results of this study indicate that center of social welfare (Puskesos) in Bandung Regency have implemented integrated social protection. Beneficiary families also considered that officers were able to provide new information as an effort to solve problems. The existence of Puskesos provides convenience and time effectiveness for beneficiary families due to the one-stop service. This one-stop service proves that there is coordination and communication between related agencies. This collaboration is supported by the commitment of various parties, such as stakeholders in Bandung Regency from local stakeholders at the village level to Puskesos officials themselves. However, in infrastructure aspect, some beneficiary families felt they were not satisfied with infrastructure, such as the comfort when they were about to submit a complaint.